2005
DOI: 10.1017/s095375620400139x
|View full text |Cite
|
Sign up to set email alerts
|

Towards a phylogenetic classification of Cordyceps: ITS nrDNA sequence data confirm divergent lineages and paraphyly

Abstract: The ascomycetous genus Cordyceps accommodates endoparasitic species that attack arthropods or other fungi. Analyses of ITS nrDNA sequence data of 72 taxa from the teleomorph genera Cordyceps, Claviceps, Epichloe¨, and the anamorph genera Akanthomyces, Beauveria, Metarhizium, Hirsutella, Hymenostilbe, Paecilomyces, Polycephalomyces, and Tolypocladium assigned the taxa to four main evolutionary lineages not reflected in the current classification of Cordyceps. Ten subclades were recognized from separate analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 101 publications
3
76
1
1
Order By: Relevance
“…Based on b-tubulin analysis, we have observed that Hirsutella grouped with a branch that included C. bassiana, suggesting that this genus possesses affinities to the Hypocreales. Stensrud et al (2005) reported that Cordyceps species are commonly the teleomorphic stage of anamorph genera of many entomopathogenic fungi. The connection of Hirsutella and Cordyceps was first observed for the ant pathogen Cordyceps unilateralis whose anamorph is Hirsutella formiacarum (Petch, 1924) and several other Cordyceps species have been reported to be the teleomorphs of various Hirsutella species (Kendrick and Carmichael, 1973;Samson et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Based on b-tubulin analysis, we have observed that Hirsutella grouped with a branch that included C. bassiana, suggesting that this genus possesses affinities to the Hypocreales. Stensrud et al (2005) reported that Cordyceps species are commonly the teleomorphic stage of anamorph genera of many entomopathogenic fungi. The connection of Hirsutella and Cordyceps was first observed for the ant pathogen Cordyceps unilateralis whose anamorph is Hirsutella formiacarum (Petch, 1924) and several other Cordyceps species have been reported to be the teleomorphs of various Hirsutella species (Kendrick and Carmichael, 1973;Samson et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…There has been no thorough study of the collections of C. gunnii from China and Tasmania (Stensrud et al 2005, Sung et al 2007a. Only one publication (Liu et al 2002) suggested Chinese C. hawkesii and C. gunnii are conspecific based on 5.8S-ITS rDNA sequences.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…There are estimated to be more than 400 species names under Cordyceps (Mains 1958, Stensrud et al 2005 although this is expected to be an underestimation of the *Corresponding author: pelizza@cepave.edu.ar extant global diversity (Hawksworth & Rossman 1997). A phylogenetic classification based on molecular data separated the species across three families, Cordycipitaceae, Clavicipitaceae and Ophiocordycipitaceae (Sung et al 2007b, Sanjuan et al 2014.…”
Section: Introductionmentioning
confidence: 99%